Blasting Vibration Generated by Breaking-Blasting Large Barriers with EBBLB - Wang Zhen-xiong; Gu Wen-bin; Liang Ting; Liu Jian-qing; Xu Jing-lin; Liu Xin (Shock and Vibration)
Equipment for breaking and blasting large barriers (EBBLB) is new break-blast equipment, which inevitably induces ground vibration and may cause substantial damage to rock mass and nearby structures as well as human beings. The ground vibration induced by break-blast is one of the inevitable outcomes. By monitoring vibration at measuring points at different distances from blasting center, time history curve of vibrating velocity can be obtained; it can be drawn that blasting seismic waves are generated mainly from the explosion of the precharge. Furthermore, different approaches have been adopted to fit relationship between particle peak velocity (PPV) and distance from blasting center, comparative analysis of which provides the most appropriate relation expression to predict attenuation of PPV of vibration with distance from blasting center. The relation between vibration frequency and distance from blasting center is obtained by Fourier transform. And the research decomposes vibrating signals in vertical direction of different distances from blasting center with Hilbert-Huang Transform (HHT), extracting information of empirical mode components of blasting vibration signals; thus vibrating signals are contracted by spectrum information and energy information, three-dimensional energy, and energy attenuation of vibration with different distances from blasting center. The study can predict ground vibration generated by EBBLB and assess its damaging effects of blasting vibration for security and protection.